2016
DOI: 10.1038/mt.2016.150
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vector Gene Therapy Protects XCGD Mice From Acute Staphylococcus aureus Pneumonia and Inflammatory Response

Abstract: Chronic granulomatous disease (CGD) is a primary immunodeficiency due to a deficiency in one of the subunits of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase complex. CGD patients are characterized by an increased susceptibility to bacterial and fungal infections, and to granuloma formation due to the excessive inflammatory responses. Several gene therapy approaches with lentiviral vectors have been proposed but there is a lack of in vivo data on the ability to control infections and inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Gene-replacement therapy in hematopoietic stem cells requires integrating vectors to ensure long term gene expression. Although more recently non-viral transposon vectors have been used [39][40][41] , the vast majority of clinical trials employed γ-retroviral 53,54 and lentiviral vectors [55][56][57] . All integrating vectors insert semirandomly throughout the genome, each having a specific integration pattern dictated by distinct features of different genomic regions 39,58,59 .…”
Section: Vectors Of Choice For Gene Replacement Therapy In Hematopoietic Stem Cellsmentioning
confidence: 99%
“…Gene-replacement therapy in hematopoietic stem cells requires integrating vectors to ensure long term gene expression. Although more recently non-viral transposon vectors have been used [39][40][41] , the vast majority of clinical trials employed γ-retroviral 53,54 and lentiviral vectors [55][56][57] . All integrating vectors insert semirandomly throughout the genome, each having a specific integration pattern dictated by distinct features of different genomic regions 39,58,59 .…”
Section: Vectors Of Choice For Gene Replacement Therapy In Hematopoietic Stem Cellsmentioning
confidence: 99%
“…In addition, Newman has served as a valuable measuring stick for assessing the therapeutic efficacy of agents designed to protect the host from S. aureus infection. The importance of Newman has been demonstrated by multiple studies in animals that have shown reduced S. aureus-caused lethality in cohorts treated with a number of different therapies (12,(14)(15)(16)(17)(18)(19)(20). In our own attempts to develop a therapeutic agent to treat S. aureus infection, we discovered significant inconsistencies in the virulence profiles of Newman strains and a derivative thereof, Newman D2C.…”
mentioning
confidence: 93%
“…Concomitant with the demand to develop an effective antistaphylococcal therapy is the need to select the most applicable model(s) for studying disease caused by S. aureus. S. aureus strain Newman (here referred to as Newman) is a commonly used model strain for studying S. aureus pathogenesis (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and in turn has been extensively used to examine the therapeutic efficacy of agents designed to treat S. aureus infection (12,(14)(15)(16)(17)(18)(19)(20). Newman was originally isolated from a human patient in 1952 (21,22) and has since been a fixture in the investigation of S. aureus pathogenesis due in large part to its strong virulence in both animal models and human ex vivo systems.…”
mentioning
confidence: 99%
“…26 GT mediated by MSP.Gp91.2T-transduced HSPCs was effective in protecting XCGD mice from S. aureus pulmonary infection. 27 Despite the extensive investigation of the efficacy of HSPC GT for XCGD in cells and mouse model systems, there is little information about long-term (>5 months) safety and efficacy in non-clinical studies with LV-mediated GT for XCGD. 24,25 Also, insertional genotoxicity has been conducted by transplanting LV-transduced Lin À cells isolated from CD45.2 C57BL/6 mice into CD45.1 recipients followed up to 26 weeks.…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 23 Different LVs encoding human Gp91 phox under the control of a myeloid-specific promoter (MSP) have been developed, and their efficacy was tested in preclinical models. 24 , 25 , 26 , 27 Transduction of mouse BM-derived XCGD lineage-negative (Lin − ) cells and human XCGD CD34 + HSPCs with an LV encoding Gp91 phox under a synthetic chimeric myeloid promoter (pCCLchimGp91 s ) drove higher Gp91 phox expression and NADPH activity in myelomonocytic cells (i.e., neutrophils) and myeloid cell progenitors compared with lymphoid cells in vitro and in vivo . 24 Therapeutic efficacy and no evidence of toxicity were reported in a preclinical study performed according to Good Laboratory Practice (GLP) using a clinical-grade G1XCGD LV to transduce human CD34 + XCGD cells and mouse XCGD Lin − cells.…”
Section: Introductionmentioning
confidence: 99%